3-Hexyl-2, 5-diphenylthiophene:phenylene vinylene-based conjugated polymer for solar cells application. (September 2017) - Mehmood, Umer; Mansha, Muhammad; Ullah, Nisar
Abstract: A conjugated polymer, poly(3-hexyl-2, 5-diphenylthiophene)-p-bisdodecyloxy-phenylene vinylene) (CP ) was synthesized whose chemical structure was confirmed by 1 H-NMR and FTIR.CP possesses electrochemical band gap of 2.19 eV, determined by cyclic voltammetry (CV), and low laying highest occupied molecular orbital (HOMO) energy level (5.24 eV). Acting as an electron donor, CP was mixed with electron acceptor PC61 BM in (1:1, w/w) to fabricate the photoactive layer. The resultantCP :PC61 BM (1:1, w/w) based polymer solar cell (PSC) under AM 1.5G (100 mWcm − 2 ) showed power conversion efficiency (PCE) of 2.66% with an open-circuit voltage ( V OC ) of 678 mV, a short circuit current density ( J SC ) of 7.711 mA/cm 2 and a fill factor (FF) of 50%. Band gap ofCP calculated by Density functional theory (DFT) measurement was determined to 2.04 eV, which was in good agreement with the experimental value obtained by CV. Highlights: Synthesis of thiophene:phenylene vinylene-based conjugated polymer (CP ). Characterization ofCP by 1 H-NMR and FTIR. Electrochemcial and computed band gaps calculation ofCP by CV and DFT, respectively. The device based onCP :PC61 BM (1:1, w/w) showed power conversion efficiency (PCE) of 2.66%.